The Role of Problem-Based Learning with The Help of Virtual Laboratory in Physics Learning: A Systematic Literature Review - Muizzatul Islamiyah; Sujito Sujito; Nasikhudin Nasikhudin (Jurnal Ilmiah Pendidikan Fisika, 2025)
The abstract nature of physics concepts and the low level of student interest often present significant challenges in the learning process. The integration of Problem-Based Learning (PBL) with virtual laboratories is believed to offer a promising solution; however, comprehensive and systematic studies on this integration remain scarce. This study aims to conduct a systematic review of the trends, methods, and key findings of studies integrating the Problem-Based Learning model with virtual laboratories in physics education in Indonesia. Using the PRISMA guidelines and a systematic literature review (SLR) approach, we analyzed 28 articles selected from the Scopus, Semantic Scholar, and Google Scholar databases using content analysis methods and visualized the results with VOSviewer software. The results of the review indicate that integrating PBL and virtual laboratories consistently improves student learning outcomes, especially critical thinking, problem-solving, scientific processes, and physics concept understanding. These results confirm that PBL supported by interactive simulations creates a more active, exploratory learning environment. Most studies employed experimental and developmental approaches, indicating a focus on testing effectiveness and developing innovative teaching tools. These findings imply the necessity of further research on other technology-based PBL approaches, such as STEM or web-based PBL, as well as the development of authentic assessment tools that can support adaptive and sustainable physics learning in the digital age.